A Snow Density Dataset for Improving Surface Boundary Conditions in Greenland Ice Sheet Firn Modeling - Fausto, Robert S.; Box, Jason E.; Vandecrux, Baptiste; van As, Dirk; Steffen, Konrad; MacFerrin, Michael J.; Machguth, Horst; Colgan, William; Koenig, Lora S.; McGrath, Daniel; Charalampidis, Charalampos; Braithwaite, Roger J. (Frontiers in Earth Science, 2018)
The surface snow density (SSD) of glaciers and ice sheets is of fundamental importance in converting volume to mass in both altimetry and surface mass balance studies, yet it is often poorly constrained. Site-specific SSDs are typically derived from empirical relations based on temperature and wind speed. These parameterizations commonly calculate the average density of the top meter of snow, thereby systematically overestimating snow density at the actual surface. Therefore, constraining SSD to the top 0.1 m can improve boundary conditions in high-resolution firn-evolution modeling. We have compiled an extensive dataset of 200 SSD point measurements from firn cores and snow pits on the Greenland ice sheet. We find that SSD within 0.1 m of the surface has an average value of 315 kg m-3 with a standard deviation of 44 kg m-3, and has an insignificant annual air temperature dependency. We demonstrate that two widely-used SSD parameterizations dependent on temperature systematically overestimate SSD over the Greenland ice sheet by 17-19%, and that using a constant density of 315 kg m-3 may give superior results when applied in surface mass budget modeling.